Perilaku Individu Dalam Organisasi - Danandjaya, Kusmana (Jurnal Literasi Pendidikan Nusantara, 2020)
The behavior has a broad definition. Behavior can be interpreted as the actions or activities of the human being himself who has a very wide expanse, among others: walking, talking, crying, laughing, working, lecture, writing, reading, and so on. Behavior is also interpreted as a response or reaction of a person to stimulus or stimulus from outside one of the Organization's environment. The implementation of the organizational plan depends largely on the individual characteristics contained in the organization. Organizations need to understand more about the characteristics and attitudes and behaviors of each individual. It must be realized and accepted that human beings are destined not to be the same, both in terms of their biological background, educational background, to the various factors that influence each individual characteristic. Therefore, the diversity of the individual has become an inevitability, and it cannot be denied its existence. This paper discusses how individual behaviors in the organization with sub-discussion of approaches in understanding human nature consisting of cognitive approaches, satisfaction approaches, strengthening approaches and psychoanalysis approaches.